Structured leadership development programmes: an enabler towards talent sustainability in higher education - Horne, A.; Newman, R.; Wright, B. (South African Journal of Higher Education, 2026)
Managing talent has become increasingly critical in today’s dynamic and competitive work environment. Higher education institutions are not excluded from this challenge and have an important responsibility to attract, develop and retain the best talent in support of providing quality education. Effective talent management efforts are, therefore, essential to creating long-term institutional talent sustainability. Various strategies and practices are employed by institutions to acquire, develop and retain their talent. In support of these efforts, higher education institutions often spend considerable resources on developing their talent without adequately assessing and knowing the benefit of these efforts. This study explores the impact of structured leadership development programmes as a talent development initiative on employees’ career advancement, retention, and performance within a higher education institution. A longitudinal study and a comparative analysis of numeric data was conducted. Two hundred and thirty-six (236) employees’ career and performance progress were tracked over a period of ten years after they successfully completed a structured leadership development programme. Employee data from the institution’s human resource database was analysed against important talent management criteria and indicators such as leadership capacity, employee performance, employee retention, succession planning and employee promotability. The study revealed that targeted talent development initiatives, such as structured leadership development programmes, forming part of a comprehensive talent management strategy, can contribute towards long-term talent sustainability in higher education institutions.